The story of the fly: quran stories for little believers - Khan, Saniyasnain (Goodword Books India, 2002)
"The Story of the Fly" from the Quran illustrates the insignificance of false idols compared to Allah's power. It recounts an incident where people are challenged to create a fly, highlighting human limitations and the importance of recognizing God's supremacy. The narrative teaches young believers about faith, humility, and the futility of worshipping anything other than the one true God.